Worldwide Mycotoxins Exposure in Pig and Poultry Feed Formulations - Philippe Guerre (Toxins, 2016)
The purpose of this review is to present information about raw materials that can be used in pig and poultry diets and the factors responsible for variations in their mycotoxin contents. The levels of mycotoxins in pig and poultry feeds are calculated based on mycotoxin contamination levels of the raw materials with different diet formulations, to highlight the important role the stage of production and the raw materials used can have on mycotoxins levels in diets. Our analysis focuses on mycotoxins for which maximum tolerated levels or regulatory guidelines exist, and for which sufficient contamination data are available. Raw materials used in feed formulation vary considerably depending on the species of animal, and the stage of production. Mycotoxins are secondary fungal metabolites whose frequency and levels also vary considerably depending on the raw materials used and on the geographic location where they were produced. Although several reviews of existing data and of the literature on worldwide mycotoxin contamination of food and feed are available, the impact of the different raw materials used on feed formulation has not been widely studied.